Using ubiquitous data to improve smartwatches' context awareness: a case study applied to develop wearable products. (29th January 2020) - Qu, Qing-Xing; Song, Yuankun
Most recently, a large amount of data is being generated by various applications on smart devices, which could contain abundant information related to the user's daily lives. This study aims to investigate whether the use of ubiquitous data could effectively improve smartwatches' context awareness. A prototype of a context-aware system consisting of an Android application and a web application was developed, and an experiment in which 20 participants were recruited to complete several tasks with a smartwatch was conducted. The results showed that the smartwatch with the prototype application successfully decreased the effort cost (operations), task completion time and error rate by making use of ubiquitous data to capture users real-time contexts and automatically execute corresponding operations. Moreover, users with a proposed context-aware system could have better user experience and more positive affective responses than the non-context-aware system. Furthermore, findings in this study could give a better understanding and suggestions to designers when they intend to design a new smartwatch or improve an existing application on a smartwatch with the use of ubiquitous data.